Caracterização experimental do escoamento bifásico de gás-líquido descendente em golfadas em tubulações levemente inclinadas - Rodrigues, Romulo Luis de Paiva (2015)
Downward slug flow in ducts of circular cross section is a frequently observed flow regime in oil and gas transportation lines. The onset of this kind of flow is due to instabilities generated by irregular pipe topography. Therefore, to understand the hydrodynamics of the slug flow is paramount in the design of crude oil production lines as well as in the project of equipment involved in oil and gas operations. The goal of this work is to experimentally analyze and characterize the two-phase gas-liquid intermittent downward flow in ducts with inclination angles of 0°, −4°, −7°, −10° and −13°. The analysis was performed at different gas-liquid volumetric flow rates for which the slug flow regime was observed. An existing experimental rig in the NUEM/UTFPR labs was used to collect data. A pair of wire-mesh sensors to evaluate the flow structure, thus obtaining void fraction temporal series was employed. From those series, statistical distributions for the characteristic parameters of such slug flows – namely the elongated bubble translational velocity, the unit cell frequency, the liquid slug and the elongated bubble lengths and the void fraction in the elongated bubble region – were obtained. The processed signals were analyzed so as to identify the relationship between the slug flow parameters, their statistical distributions and averaged values alike as functions of the flow rates and fluid properties. Correlations for slug frequency, elongated bubble velocity, liquid slug and bubble lengths as well as empirical expressions for the void and liquid fractions were developed, all within a confidence interval of 95%. It is expected that such correlations may contribute to the betterment of future engineering endeavours, and used in the development of similar mathematical models.